2001
DOI: 10.1161/01.str.32.6.1349
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Acute Ischemic Stroke Trials Through the 20th Century

Abstract: Background and Purpose-The advent of controlled clinical trials revolutionized clinical medicine over the course of the 20th century. The objective of this study was to quantitatively characterize developments in clinical trial methodology over time in the field of acute ischemic stroke. Methods-All controlled trials targeting acute ischemic stroke with a final report in English were identified through MEDLINE and international trial registries. Data regarding trial design, implementation, and results were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
162
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 51 publications
(28 reference statements)
1
162
0
4
Order By: Relevance
“…As expected, all assessed variables demonstrated improvements from the fi rst to the third month after the CVA. Th is observed functional recovery was related to the reversal of edema and biochemical alterations in the interstitial area of the injury 34 , as well as to the neural reorganization resulting from the demands of daily life and rehabilitation training 1,3,9,24,33 .…”
Section: Discussionmentioning
confidence: 97%
“…As expected, all assessed variables demonstrated improvements from the fi rst to the third month after the CVA. Th is observed functional recovery was related to the reversal of edema and biochemical alterations in the interstitial area of the injury 34 , as well as to the neural reorganization resulting from the demands of daily life and rehabilitation training 1,3,9,24,33 .…”
Section: Discussionmentioning
confidence: 97%
“…Emblematic of the high morbidity and mortality associated with stroke are the failures of potential stroke therapeutics, which showed benefit in small animal rodent stroke models but failed to translate into clinical success (Kidwell et al, 2001). As a result, rodent stroke models have been criticized for the anatomical disparity between small and large mammalian brains, large variability in infarct volumes, and inaccurate methods of inducing and confirming arterial occlusion (Gerriets et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have demonstrated that orally supplemented aTCT protects against stroke-induced lesion in the brain of spontaneously hypertensive rats (Khanna et al, 2005b). As small animal studies are recognized to be of limited reliability to predict success for stroke therapeutics in clinical trials (Kidwell et al, 2001), we developed a minimally invasive preclinical canine model (Rink et al, 2008) to test the efficacy of a tocotrienolenriched (TE) supplement in a randomized, blind, placebo (PBO)-controlled setting. Angiography, enabled in our large animal setting, helped elucidate that prophylactic TE supplementation improves collateral blood flow to the stroke-affected territory during stroke.…”
Section: Introductionmentioning
confidence: 99%
“…If there is one trait my generation of stroke researchers has acquired, it is a sense of humility. 9 Over the course of my career, I n a decade after approval of IV rt-PA for acute stroke, treatment leads to good outcomes in less than half of patients, and hemorrhage rates have not been reduced. Recanalization improves outcome 1 but is often delayed and incomplete.…”
mentioning
confidence: 99%